2016
DOI: 10.1111/bju.13545
|View full text |Cite
|
Sign up to set email alerts
|

De Ritis ratio (aspartate transaminase/alanine transaminase ratio) as a significant prognostic factor after surgical treatment in patients with clear‐cell localized renal cell carcinoma: a propensity score‐matched study

Abstract: An elevated AST/ALT ratio was significantly associated with worse postoperative survival in patients surgically treated for localized clear-cell RCC. Further prospective studies are needed to understand the prognostic value of preoperative AST/ALT ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 24 publications
1
77
1
1
Order By: Relevance
“…Lee et al . also identified a higher AST/ALT ratio as a valuable prognostic marker of progression‐free survival (HR 1.37), CSS (HR 1.97) and OS (HR 1.56), particularly in patients with clear cell histology . Interestingly, Japanese researchers recently investigated 68 patients with mRCC who had undergone cytoreductive radical nephrectomy, and through propensity score matching analyses, reported that the preoperative De Ritis ratio was a significant prognosticator .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al . also identified a higher AST/ALT ratio as a valuable prognostic marker of progression‐free survival (HR 1.37), CSS (HR 1.97) and OS (HR 1.56), particularly in patients with clear cell histology . Interestingly, Japanese researchers recently investigated 68 patients with mRCC who had undergone cytoreductive radical nephrectomy, and through propensity score matching analyses, reported that the preoperative De Ritis ratio was a significant prognosticator .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to non‐malignant diseases, these markers and the relative ratio of AST to ALT, often referred to as the De Ritis ratio, have been suggested as valuable prognostic factors in patients with hepatocellular carcinoma or liver metastasis . Furthermore, recent studies have shown that the preoperative AST/ALT ratio is an independent predictor of survival outcomes in patients who have undergone nephrectomy for RCC . AST and ALT production might be influenced by cancer‐related changes in metabolism, and therefore, this biomarker is a potentially valuable prognosticator in patients with mRCC.…”
Section: Introductionmentioning
confidence: 99%
“…AAR was subsequently used to predict the presence of progressive fibrosis in chronic hepatic B patients and poor survival in chronic viral hepatitis C 24. In recent years, AAR has been shown to be a useful predictor for nonhepatic diseases and a prognostic biomarker in certain types of malignant tumor 11,1416,24–27. For example, in a large European cohort of nonmetastatic renal cell carcinoma patients, Bezan et al identified preoperative AAR as a predictor of a poor clinical outcome 11.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that ALT is primarily enriched in liver tissue, while AST is widely distributed in diverse organs such as the brain, kidney, muscle, and even the heart. This could result in AST remaining in a higher proliferative state than ALT, even when the condition of the patient is deteriorating 11,15,16,24. Among patients with a poor outcome, the decrease in the ALT level was larger than that for AST, resulting in a higher AAR being related to a poor outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation